Analysis of Manado City Tourism Management Policy - Tangian, Diane; Polii, Bernadain D.; Mengko, Seska M.H. (AIBPM Publisher, 2021)
The tourism industry has an important role to improve economic and community welfare. In several regions, the industry boosts the regional economy as the main income source. Realizing this, the government has been currently trying to develop tourism potentials in their respective areas. North Sulawesi is one of the priorities for developing tourist destinations by the central government, and one of the tourist objects is Likupang. By setting Likupang as one of the priorities for developing tourist destinations, it will afford opportunities for the City of Manado to increase revenue from the tourism sector. Thus, a tourism management policy is needed to harmonize environmental, socio-cultural, and economic aspects. Manado City tourism management policy is assessed with The Exponential Comparison Method (MPE) by looking at the degree of importance based on experts’ opinions. Overall policy assessment refers to four aspects, namely environmental, socio-cultural, economic, and political aspects. Based on the weighting results, the availability of employment has the highest value. Meanwhile, for the assessment of alternative policies, the first integrated management policy between the main tourist objects around has the highest value.